(untitled) (Research, Society and Development, 2021)
Context: in Brazil, the use of behavioral interventions (BI) in public policies (PP) is still incipient. Objective: the present work aims to analyze BI, in a pioneering experience in the use of Behavioral Economics (BE) in the design of PP in Brazil, created to institute the supplementary pension scheme of federal public servants. Methods: the case study was carried out using data from FUNPRESP portals, Transparency and PEP Panel and document analysis. In the qualitative approach, legal hermeneutics was used to interpret the meaning and application of the norms involved in the study, seeking to expand the possibilities of their understanding. Results: indicate that BI contributed to the significant increase in the number of participants in the supplementary pension plan and the increase in voluntary participation through campaigns that mitigated the effects of heuristics and cognitive biases predominant in the decision-making process related to the adoption of pension plans. Conclusions: thus, it is evidenced that the use of BE knowledge in social security enhances the results of the policy. However, because it is the analysis of a specific case, there is insufficient evidence to generalize the effectiveness of behavioral interventions in public policies.